Explicație pas cu pas:
a²+4a+b²-6b+13=0 =>
a²+4a+4+b²-6b+9=0 =>
(a+2)²+(b-3)²=0 <=> (a+2)²=0 si (b-3)²=0 pt ca ambii termeni sun pozitivi
=> a= -2 si b=3
a²+b²+2(a+2b)+5=0 =>
a²+b²+2a+4b+5=0 =>
a²+2a+1+b²+4b+4=0 =>
(a+1)²+(b+2)²=0 => (a+1)²=0 si (b+2)²=0 =>
a= -1 si b= -2
a²+2V3a+b²+4V2b+11=0=>
a²+2V3a+3+b²+4V2b+8=0 =>
(a+V3)²+(b+2V2)²=0 =>(a+V3)²=0 si (b+2V2)²=0 =>
a= -V3 si b= -2V2
2a²+2V2a+3b²+2V3b+2=0 =>
2a²+2V2a+1+3b²+2V3b+1=0 =>
(V2a+1)²+(V3b+1)²=0 =>(V2a+1)²=0 si (V3b+1)²=0 =>
a= -V2/2 si b= -V3/3